Design of Value Chains for Microalgal Biorefinery at Industrial Scale: Process Integration and Techno-Economic Analysis - Slegers, Petronella M.; Olivieri, Giuseppe; Breitmayer, Elke; Sijtsma, Lolke; Eppink, Michel H. M.; Wijffels, Rene H.; Reith, Johannes H. (Frontiers in Bioengineering and Biotechnology, 2020)
The objective of this work was to identify industrial scenarios for the most promising microalgal biorefinery value chains on the basis of product selection, yields and techno economic performance, using biological characteristics of algae species. The development, value creation and validation of several new processing routes with applications in food, aquafeeds and non food products were particularly considered in this work. The techno economic performance of various single and multiproduct value chains was evaluated for 4 industrial microalgal strains. Cost-revenue optimization was done for a 10 kton microalgal dry weight y–1 simulated biorefinery plant, using flow sheeting software for equipment sizing, mass and energy flow modelling and subsequent techno economic evaluation. Data on yield, material and energy consumption were based on pre- and pilot size production plants (TRL 5 6). Revenue optimization was accomplished by first analyzing the performance of single product value chains of the microalgal strains. Subsequently, a strategy was developed to exploit almost all biomass based on the most promising microalgal strains. The cultivation costs are most of the time the major costs of the value chains. For the single product value chains common process bottlenecks are low product yields, especially for soluble proteins where only a small fraction of the biomass is leading to economic value. The biorefinery costs (excluding cultivation) vary significantly for various species, due to the species-specific operating conditions as well as differences in product yields. For the evaluated single product value chain scenarios the costs for utilities and other inputs were in general the highest contributing expenses. A biorefinery approach significantly increases the biomass utilization potential to marketable products from 7–28% to more than 97%. Although the cascading approach increases the total production costs of the multiproduct value chains significantly, this is more than compensated by the increased overall biomass revenue. For all selected multiproduct chains there is a significant potential to become profitable at a relevant industrial scale of 10 kton per year. Additional insights in the product functionality, quality and their market size are needed to narrow down the wide range of foreseen product revenues and resulting profits.